KORELASI ETOS KERJA TERHADAP STATUS EKONOMI PETANI SAYUR DI KECAMATAN MARPOYAN DAMAI PEKANBARU - Anjani, Gallih Mayang; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aimed at knowing the correlation of the work ethos on vegetable farmers economic status in Damai Marpoyan Sub-District Pekanbaru. The research design of this study was quantitative study using correlation formula of Pearson Product Moment and using probability approach with simple random sampling technique. The data collection technique used was quantitative analysis, provided with form of table with attached explanations. The result of the research was there was a significant correlation between the work ethos on vegetable farmers economic status in Damai Marpoyan Sub-District Pekanbaru. Based on the result of this study, work ethos influences the economic status of vegetable farmers in Marpoyan Damai Sub-District.Keywords : work ethos, economic status, farmer